Smartphone applications for young English language learners - Siti Sarah, Sukor; Zuraina, Ali (IOP Publishing, 2020)
The advancement of technology has permitted the widespread use of mobile applications in English language education. Hence, the term mobile-assisted language learning or MALL appeared in the literature since the early 21stcentury. This paper highlights a study’s report on the smartphone applications’ pattern of learning English that is targeted for Muslim young English language learners (YELL). The authors decided to use systematic literature review approach to guide the mobile applications reviewing process. The availability of applications was first searched on Google Play using predetermined keywords that resulted in 250 mobile applications. Guided by the PRISMA model resulted in 26 smartphone applications that were finalised to be reviewed using the Analytical Framework of MALL. The findings demonstrated that smartphone applications are popular with vocabulary attainment that is crucial in the early stage of English language acquisition. Several interesting aspects may be explored further by including non-native Muslim YELL in MALL empirical findings, Islamic perspectives on the use of MALL for Muslim YELL’s English language development and framework development for reviewing MALL befitting Muslim learners